2021
DOI: 10.21679/arc.v8i1.209
|View full text |Cite
|
Sign up to set email alerts
|

Miedo al COVID-19 en residentes de un Asentamiento Humano en Puente Piedra, Lima

Abstract: Objetivos: Identificar el miedo al COVID-19 en residentes de un Asentamiento Humano en Puente Piedra, Lima. Materiales y métodos: Esta investigación fue desarrollado desde el enfoque cuantitativo, su diseño fue descriptivo-transversal. La población estuvo conformada por 500 participantes. La técnica de recolección de datos fue la encuesta y el instrumento de medición fue la Escala de Miedo al COVID-19 (FCV-19S), que consta de 7 ítems y 2 dimensiones. Resultados: En cuanto a los participantes, los varones repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…In Germany, an investigation was carried out and determined that women were more likely to be more concerned and anxious compared to men with regard to contracting COVID-19 [ 19 ]. Likewise, an investigation was carried out in Peru and found that women were characterized by having high levels of fear of contagion, while low and moderate levels predominated in men [ 25 ]. On the other hand, an investigation carried out in Mexico reported that women had a greater fear of being infected with COVID-19 than men, which was consistent with international reports on mental health that indicated that there was a higher prevalence of anxiety disorders and depression among women [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, an investigation was carried out and determined that women were more likely to be more concerned and anxious compared to men with regard to contracting COVID-19 [ 19 ]. Likewise, an investigation was carried out in Peru and found that women were characterized by having high levels of fear of contagion, while low and moderate levels predominated in men [ 25 ]. On the other hand, an investigation carried out in Mexico reported that women had a greater fear of being infected with COVID-19 than men, which was consistent with international reports on mental health that indicated that there was a higher prevalence of anxiety disorders and depression among women [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several existing studies showed that when there is an elevated risk of infection, people may develop widespread fears about their health and that of their family members. (9,10) Fear of COVID-19 is a negative emotional reaction or persistent worry about an impending public health event. (11,12) In a study carried out in Portugal, with 1122 inhabitants, they stated in their results that the levels of fear were high since they were related to anxiety and depression due to the perception that the inhabitants have before COVID-19 and that factors that emotional fear and fear of going to some service facilities during the pandemic, It generated fear in people.…”
Section: Introductionmentioning
confidence: 99%
“…Es importante poder conocer que la información brindada por parte de los médicos durante la encuesta realizada el 94.1% manifiestan tener miedo al COVID-19 se puede relacionar con Castillo en estudio realizado por la revista de investigación científica ágora, donde se resalta que un nivel alto de personal médico tiene miedo a fallecer por COVID-19 12 .…”
unclassified